2015
DOI: 10.1002/2014ja020823
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the equatorial and low‐latitude ionospheric response to an intense X‐class solar flare

Abstract: We have investigated the ionospheric response close to the subsolar point in South America due to the strong solar flare (X2.8) that occurred on 13 May 2013. The present work discusses the sudden disturbances in the D region in the form of high-frequency radio wave blackout recorded in ionograms, the E region disturbances in the form of the Sq current and equatorial electrojet intensifications, and the enhancement and decay in the ionospheric total electron content (TEC) as observed by a network of Global Navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 39 publications
(63 reference statements)
5
33
0
Order By: Relevance
“…Extensive studies have been carried out to investigate the solar flare effects on the ionosphere [e.g., Afraimovich et al, 2001;Le et al 2007Le et al , 2013Le et al , 2016Leonovich et al, 2002;Liu et al, 2004;Mendillo and Evans, 1974;Nogueira et al, 2015;Tsurutani et al, 2005;Wan et al, 2005;Xiong et al, 2011;Zhang and Xiao, 2005;Zhang et al, 2011]. These studies showed that the ionospheric responses to solar flares can be interpreted by the photochemical processes resulted from the increased solar X-rays and EUV [Liu et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive studies have been carried out to investigate the solar flare effects on the ionosphere [e.g., Afraimovich et al, 2001;Le et al 2007Le et al , 2013Le et al , 2016Leonovich et al, 2002;Liu et al, 2004;Mendillo and Evans, 1974;Nogueira et al, 2015;Tsurutani et al, 2005;Wan et al, 2005;Xiong et al, 2011;Zhang and Xiao, 2005;Zhang et al, 2011]. These studies showed that the ionospheric responses to solar flares can be interpreted by the photochemical processes resulted from the increased solar X-rays and EUV [Liu et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned, the photochemical process could not have produced the anomaly distribution of ionospheric responses during the six solar flares. In addition, some studies have suggested that the electrodynamic process at low latitudes could have been influenced by the sudden enhancements in solar irradiances (e.g., Qian LY et al, ; Nogueira et al, ; Zhang RL et al, ), which could have caused a weaker eastward electric field and a weakened equatorial ionization anomaly (EIA) crest structure. The two EIA crests would be located at the lower latitudes.…”
Section: Resultsmentioning
confidence: 99%
“…It is also interesting to observe that the amplitude of maximum is larger at the magnetic equator; however it is not sorted by dip angle. Nogueira et al (2015) had observed such delay, but no detailed analysis or interpretation was attempted. In an attempt to obtain a better clue on the nature of the delay and to seek an understanding of its possible cause, in the present work, we have carried out detailed modeling with sufficient temporal and spatial resolutions of the E-layer conductivities during the course of the flare.…”
Section: Observational Datamentioning
confidence: 99%
“…These disturbances are observed in the form of sudden increases in the ionospheric electron density in the D, E and F regions, reflecting in the ionospheric currents (Curto et al 1994a, b, Xiong et al, 2011Tsurutani et al, 2005;Manju et al, 2009;Nogueira et al, 2015;Abdu et al, 2017). The equatorial electrojet (EEJ) current system is also disturbed due to sudden increase in the solar ionizing radiation flux.…”
Section: Introductionmentioning
confidence: 99%